Getting Schooled: Legal Mobilization as an Educative Process. Issue 1 (20th May 2016) - Gallagher, Mary; Yang, Yujeong
Abstract : This article explores the role of formal education and specific legal knowledge in the process of legal mobilization. Using survey data and in‐depth case narratives of workplace disputes in China, we highlight three major findings. First, and uncontroversially, higher levels of formal education are associated with greater propensity to use legal institutions and to find them more effective. Second, informally acquired labor law knowledge can substitute for formal education in bringing people to the legal system and improving their legal experiences. The Chinese state's propagation of legal knowledge has had positive effects on citizens' legal mobilization. Finally, while education and legal knowledge are factors that push people toward the legal system, actual dispute experience leads people away from it, especially among disputants without effective legal representation. The article concludes that the Chinese state's encouragement of individualized legal mobilization produces contradictory outcomes—encouraging citizens to use formal legal institutions, imbuing them with new knowledge and rights awareness, but also breeding disdain for the law in practice.